Sellar Glomus Tumor Misdiagnosed as Pituitary Adenoma: A Case Report and Review of the Literature - Cheng, Yijun; Tang, Hao; Wu, Zhe Bao (Frontiers in Endocrinology, 2022)
Glomus tumor is a rare mesenchymal tumor with an organ-like structure. Sellar glomus tumors are extremely rare with only 6 reported cases in the literature. Due to the lack of special clinical manifestations and imaging features, the disorder may be easily misdiagnosed as other sellar tumors, especially pituitary adenomas. Herein, the present study showed a case of a 69-year-old male with hypopituitarism who was preliminarily misdiagnosed as nonfunctional pituitary adenoma.